Commission staff paper explores the implications of reform options for sugar - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
The Commission staff paper 'Reforming the European Union's Sugar Policy: Summary of Impact Assessment Work', looks at...